Profiling the Competence of Chemistry Education Students at FKIP UNTAN in Designing Technology-Based Instruction - Dorkas, Marselka Meilani; Enawaty, Eny; Erlina (Universitas Pendidikan Mandalika, 2025)
In the modern era and with the implementation of the Merdeka Curriculum, teachers are expected to adopt a different approach to learning by designing IT-based instruction. Education students, as prospective teachers, are expected to utilize technology to design and develop active and engaging learning experiences. This study aims to examine the competency profile of Chemistry Education students from the Faculty of Teacher Training and Education at Tanjungpura University, specifically the 2021 cohort, with a total of 45 respondents. The research method used is quantitative descriptive, with participants selected using a saturated sampling technique. Data collection techniques include a student competency profile questionnaire on IT-based learning design, a 21st-century skills implementation questionnaire, observation sheets of learning module designs, and unstructured interviews. Data were analyzed using descriptive quantitative methods. The results show the percentage scores for each aspect as follows: critical thinking and evaluation – 84%, e-safety – 85%, information, media, and technology skills – 84%, communication and collaboration skills – 89%, and creativity – 88%. Each of these aspects falls into the